Nutritional quality assessment of complementary food from plantain, velvet bean and crayfish (International Journal of Scientific Research and Management (IJSRM), 2023)
Complementary foods are needed to supplement breast milk with essential nutrients needed for general wellbeing of growing children. In developing countries these children still suffer from nutritional deficiencies which can be ameliorated by development of nutrient dense and acceptable complementary foods from locally available crops. Mixture design of design expert was used to obtain optimized flour blend from plantain, velvet beans and crayfish flours for the production of complementary food which was analyzed for its nutritional and sensory qualities. This was analyzed for its proximate composition, nutritional quality and sensory properties. Result of proximate composition for moisture, crude protein, fat, fibre, ash and carbohydrate was 6.49 %, 12.18 %, 1.50 %, 0.35 %, 2.10 % and 82.93 % respectively. The complementary food had 64.80 % in-vitro protein, 21.80 % starch digestibility, gross energy of 4132.21 Cal, in-vitro total sugar content of 3.29g/100g and a total carbohydrate content of 50.87 %. The complementary food had sensory attributes comparable to commercial complementary foods, was nutrient dense and could be used as alternative to expensive complementary foods. There is therefore need to continue to formulate nutritionally dense and acceptable weaning food from local crops in order to ameliorate the nutritional deficiencies among infants and hence improve their general wellbeing.